2006
DOI: 10.1161/circulationaha.105.608968
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 Activates a Genetic Program Promoting Chamber Dilation and Contractile Dysfunction in Calcineurin-Induced Heart Failure

Abstract: Background-Hypertrophic growth, a risk factor for mortality in heart disease, is driven by reprogramming of cardiac gene expression. Although the transcription factor myocyte enhancer factor-2 (MEF2) is a common end point for several hypertrophic pathways, its precise cardiac gene targets and function in cardiac remodeling remain to be elucidated. Methods and Results-We report the existence of synergistic interactions between the nuclear factor of activated T cells and MEF2 transcription factors triggered by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
83
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 36 publications
(40 reference statements)
8
83
1
2
Order By: Relevance
“…Members of the MEF2 family are well known to critically regulate heart development and recent studies strongly support a role for this pathway in the adult heart's response to stress. For example, transgenic overexpression of MEF2A or MEF2C leads to a dosedependent dilated cardiomyopathy that is dramatically worsened following pressure overload (16,17). Consistent with this role, overexpression of a dominant-negative MEF2 normalized ventricular dimensions and contractility in calcineurin transgenic mice (16).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Members of the MEF2 family are well known to critically regulate heart development and recent studies strongly support a role for this pathway in the adult heart's response to stress. For example, transgenic overexpression of MEF2A or MEF2C leads to a dosedependent dilated cardiomyopathy that is dramatically worsened following pressure overload (16,17). Consistent with this role, overexpression of a dominant-negative MEF2 normalized ventricular dimensions and contractility in calcineurin transgenic mice (16).…”
Section: Discussionmentioning
confidence: 86%
“…Prohypertrophic stimuli activate a series of intracellular signal transduction pathways that result in the induction of MEF2 and GATA4 DNA-binding activity and nuclear accumulation of NFATs. In vitro studies have demonstrated that overexpression of either MEF2 factors or GATA4 induces cardiomyocyte hypertrophy (10,16). Cardiac-specific transgenic overexpression of either MEF2 (16,17) or constitutively active calcineurin-A (18) cause cardiomyopathies characterized by increased cardiac mass, chamber dilation, and left-ventricular systolic dysfunction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MEF2D is a member of myocyte enhancer factor-2 family of transcription factors that are activated by Ca 2+ /Calmodulin-dependent signaling pathways, and regulate expression of structural genes in the cardiocyte [20]. Although changes in MEF2 levels are relatively modest during cardiac hypertrophy, recent findings have linked MEF2 to expression of target genes associated with myocardial remodeling, for example cytoskeletal components and ion channels [21,22]. FGF-2 and VEGF are members of the heparin binding protein family of growth factors.…”
Section: Discussionmentioning
confidence: 99%